2017
DOI: 10.1016/j.coastaleng.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Entrained air in bore-driven swash on an impermeable rough slope

Abstract: The aim of the present investigation is to clarify the role and evaluate the importance of air entrainment in the swash zone by carrying out a set of detailed laboratory experiments. Experiments involved generating a single, highly repeatable, large-scale, bore-driven swash event on a sand-rough impermeable beach with slope 1:10. Measurements that yield the characteristics of the entrained air, including the void fractions, bubble size and bed-parallel bubble velocity, and the hydrodynamics are obtained at fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(92 reference statements)
1
2
0
2
Order By: Relevance
“…When comparing among the three beaches, it could be observed that the bore propagating on the steep beach (Figure 4B) results in stronger splashing water, air entrainment, and turbulence flow than those on the mild beach (Figure 4A). This is consistent with the results of O'Donoghue et al ( 2010) and Dai et al (2017) who carried out the experiments on a 1:10 beach. Moreover, the backwash encounters tail wave violently; therefore, the hydraulic jumps could be only observed on both steep and composite beaches (Figures 4B, C).…”
Section: Visualization Of the Swash Evolutionsupporting
confidence: 92%
“…When comparing among the three beaches, it could be observed that the bore propagating on the steep beach (Figure 4B) results in stronger splashing water, air entrainment, and turbulence flow than those on the mild beach (Figure 4A). This is consistent with the results of O'Donoghue et al ( 2010) and Dai et al (2017) who carried out the experiments on a 1:10 beach. Moreover, the backwash encounters tail wave violently; therefore, the hydraulic jumps could be only observed on both steep and composite beaches (Figures 4B, C).…”
Section: Visualization Of the Swash Evolutionsupporting
confidence: 92%
“…(2009) and Dai et al. (2017) are too short to reach the maximum inundation depth. The predictive formula, (5.4), estimates accurately the run-up data measured in Barnes et al.…”
Section: Numerical Simulationsmentioning
confidence: 98%
“…Dai et al. (2017) employed a similar set-up to study the entrained air in breaking bores and concluded that the effect of air bubbles on swash flows is small, supporting the assumption that the swash flows can be modelled as a single phase fluid. Lin et al.…”
Section: Introductionmentioning
confidence: 95%
“…BIV)测量了破碎区的气泡空隙率、 气泡大小和气泡速 度等的分布 [18] . 此外, 一些学者从射流实验入手对 气泡特性及其气液两相流流动特性进行研究 [19] ; 部 分学者则关注气泡特征参数与湍流之间的关系, 如 Hoque和Aoki [20] 对卷破波作用下破碎过程中气泡夹 带引起的能量耗散进行了研究, 并通过实验对气泡 空隙率进行了测量, 基于理论分析得到空隙率分布 遵循扩散方程解析解; Deike等人 [21] 提出了用于预测 破碎波气泡输运的模型, 指出波浪破碎过程中气泡 的产生量与波能损耗呈线性关系; 在此基础上, 部分 学者采用光纤探针 [22] 或电导探针 [23] 测量了波浪破碎 过程中水体掺气空隙率的时空变化特征, 并分析了 破碎区水体中的空隙率、气泡分布和湍流特性, 发现 空隙率与气泡湍流之间存在线性变化的关系.…”
unclassified
“…此外, 部分 学者基于三维数值模拟方法开展了波浪破碎作用下 气 泡 输 运 过 程 及 其 与 水 体 剪 切 相 互 作 用 机 制 的 研 究 [25,26] . 然而, 类似的在破碎区内的气液两相流特性 以及空气卷入对近岸波浪传播特性的影响等问题仍 然缺乏深入的研究 [23] , 特别是对卷破波作用下气泡 运动特性认识不足 [20] , 而前人研究指出近岸带卷破 波引起的掺气远大于溢波的作用 [18,27] , 值得深入开 展研究.…”
unclassified